THE IMPACT OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) ON THE ECONOMIC GROWTH OF ASEAN-5 COUNTRIES - Ghazali, Nur Syazwina; Mohd Daud, Siti Nurazira; Ismail, Nur Hafizah (International Journal of Research -GRANTHAALAYAH, 2023)
ESG program has become crucial for long-term value and business resiliency through efficient use of natural resources and effective policies on social and economic aspects. A country which has a good ESG performance would achieve higher economic growth. This study examines the ESG country-level performance across the ASEAN-5 by assessing the impact of ESG on economic growth. The study utilized annual data from 1990 to 2020 for five countries - Indonesia, Malaysia, the Philippines, Singapore, and Thailand. This study constructs the ESG index at the country level by employing frequency statistics of text mining and factor analysis for each country over time. Establishing an ESG country index would better reflect the ASEAN-5 nation's progress in ESG practices. Besides that, the ARDL method was employed to establish the relationship between ESG and economic growth. The results revealed mixed impacts of ESG on economic growth, which can be attributed to the variations in ESG practices and policies across the countries. Some results showed a significant positive impact of ESG practices on economic growth, while others showed no significant or negative impact. This study emphasizes the importance of a suitable ecosystem that supports the effectiveness of ESG adoption. This study recommends several precautionary policies, such as low-interest loans, grants, and tax relief, to support a firm's resilience during pandemics.